Climate-linked biogeography of mycorrhizal fungal spore traits - Smriti Pehim Limbu; Sidney L. Stürmer; Geoffrey Zahn; Carlos A. Aguilar-Trigueros; Noah Rogers; V. Bala Chaudhary (Proceedings of the National Academy of Sciences, 2025)
Climate-driven variation in traits is crucial for predicting ecological responses to environmental change, yet global patterns and drivers of microbial trait variation remain poorly understood. Using global datasets of arbuscular mycorrhizal (AM) fungal observations linked to spore morphological traits, we show that climate shapes spore trait variation and functional diversity. Larger spore volumes were more prevalent in warm, wet climates but were associated with smaller species range sizes, suggesting a trade-off between persistence and dispersal potential. Similarly, ornamented spores were more common in warm, wet climates and were associated with narrower range sizes. Cell wall investment (i.e., wall thickness relative to volume) decreased in warmer, wetter climates compared to cooler, drier ones and was the strongest predictor of species range size, with intermediate investment associated with larger geographic distributions. Spore shape and color (i.e., melanin pigmentation) also exhibited climate-driven patterns, with spherical spores and greater pigmentation more common in warm, wet climates. Phylogenetic analyses revealed high conservatism for spore ornamentation, moderate for volume, low for color, and none for shape and cell wall investment. Additionally, functional diversity analyses showed that warm, wet climates promote higher within-community trait richness but lower trait divergence, while broader climatic variability drives higher beta diversity. These findings support growing evidence that trait–environment relationships extend to microbial communities, reflecting ecological principles such as environmental filtering, evolutionary constraint, and dispersal–persistence trade-offs. Incorporating microbial traits improves predictions of biogeographic shifts and their cascading effects on plant–microbe interactions and ecosystem stability under climate change.